Benefits of multimodal enhanced recovery pathway in patients undergoing kidney transplantation. Issue 2 (26th December 2017) - Espino, Kevin A.; Narvaez, J. Reinier F.; Ott, Michael C.; Kayler, Liise K.
Abstract: Background: Use of enhanced recovery after surgery (ERAS) pathways to accelerate functional recovery and reduce length of stay (LOS) has rarely been investigated in kidney transplantation (KTX). Materials and Methods: Consecutive adult isolated KTXs between July 2015 and July 2016 (ERAS, n = 139) were compared with a historical cohort between January 2014 and July 2015 (HISTORIC, n = 95). Results: Enhanced recovery after surgery recipients were significantly more likely to receive kidneys that were non‐local (56.1% vs 4.2%), higher Kidney Donor Profile Index (36‐85, 58.4% vs 45.2%; >85, 15.2% vs 10.7%), cold ischemia time ≥30 h (62.4% vs 4.7%), induced with antithymocyte globulin (97.1% vs 87.4%), and to develop delayed graft function (46.4% vs 25.0%). LOS was shorter by 1 day among ERAS (mean 4.59) compared to HISTORIC patients (mean 5.65) predominantly due to a shift in discharges within 3 days (32.4% vs 4.2%); 30‐day readmission to the hospital (27.3% vs 27.4%) or emergency room visit (9.4% vs 7.4%) was similar. There was one 30‐day death in the ERAS group and none in the HISTORIC group. Return to bowel function and early meal consumption were significantly associated with ERAS, however, with somewhat higher diarrhea and emesis rates. Conclusion: ERAS following KTX correlated with lower LOS without change in readmissions or ER visits despite higher delayed graft function rates.